A low-cost sensor based smart and efficient health monitoring system for elderly people using internet of things - Shaown, Tamanna (Brac University, 2021)
This thesis is submitted in partial fulfilment of the requirements for the degree of Master of Science in Electrical and Electronic Engineering, 2020.